Beginning Perl - Lee, James. (Apress : Imprint: Apress, 2010)
This is a book for those of us who believed that we didn’t need to learn Perl, and now we know it is more ubiquitous than ever. Perl is extremely flexible and powerful, and it isn’t afraid of Web 2.0 or the cloud. Originally touted as the duct tape of the Internet, Perl has since evolved into a multipurpose, multiplatform language present absolutely everywhere: heavy-duty web applications, the cloud, systems administration, natural language processing, and financial engineering. Beginning Perl, Third Edition provides valuable insight into Perl’s role regarding all of these tasks and more. Commencing with a comprehensive overview of language basics, you’ll learn all about important concepts such as Perl’s data types and control flow constructs. This material sets the stage for a discussion of more complex topics, such as writing custom functions, using regular expressions, and file input and output. Next, the book moves on to the advanced topics of object-oriented programming, modules, web programming, and database administration with Perl’s powerful database interface module, DBI. The examples and code provided offer you all of the information you need to start writing your own powerful scripts to solve the problems listed above, and many more. Whether you are a complete novice or an experienced programmer, Beginning Perl, Third Edition offers an ideal guide to learning Perl.